Effect of Codonopsis Radix and Polygonati Rhizoma on the regulation of the IRS1/PI3K/AKT signaling pathway in type 2 diabetic mice - Mao, Yong-po; Song, Yi-ming; Pan, Sheng-wang; Li, Ning; Wang, Wen-xiang; Feng, Bin-bin; Zhang, Jian-hai (Frontiers in Endocrinology, 2022)
Objective: Codonopsis Radix and Polygonati Rhizoma (CRPR) showed good hypoglycemic effect. The research discussed the effect of CRPR on high-fat/high-sugar diet (HFHSD) and streptozotocin (STZ) induced type 2 diabetes mellitus (T2DM) mice, and to investigate its mechanism. Methods: Modeling T2DM mice by combining HFHSD and STZ. After the model was completed, normal and model groups received the same volume of normal saline intragastrically, and the negative control group was treated with metformin (200 mg/kg·BW). Meanwhile, four consecutive weeks of oral gavage were given for the low/medium/high (2.5, 5, and 10 g/kg·BW CRPR) dose groups during the course of the study. We measured body weight and fasting blood glucose (FBG) on a weekly basis. Using enzyme-linked immunosorbent assays (ELISA) kit to measure the serum and liver samples. By hematoxylin-eosin (H&E) staining to observe the pathological status of liver and pancreas; PI3K, p-PI3K, AKT, and p-AKT protein expression levels were examined via western blot (WB) analysis. Result: (1) In comparison to model mice, each treatment group had significantly elevated levels of FBG, total cholesterol (TC) and triacylglycerol (TG) (P＜0.01, P＜0.05); The levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were significantly reduced (P＜0.01); Fasting insulin (FINS) level was elevated in all groups of CRPR (P＜0.05), and there were significantly higher levels of high-density lipoprotein cholesterol (HDL-C) in both the low-dose and high-dose groups (P＜0.05). According to the results of H&E staining, the treatment reduced organ enlargement, improve liver lipid accumulation, and repair islet injury in T2DM mice. (2) WB analysis showed that each group of CRPR could significantly up-regulate the protein expression of IRS1, p-GSK3β, PI3K and p-Akt (P＜0.05), and significantly down-regulate p-IRS1 protein expression (P < 0.05). Conclusion: It was concluded that CRPR could effectively improve the metabolic disturbance of lipids, repair damaged liver and pancreatic tissues, and reduce insulin resistance (IR) in T2DM mice. The mechanism of action may be associated with up-regulation of IRS1/PI3K/AKT signaling pathway and inhibition of IRS1 phosphorylation.